Free-space terabit/s coherent optical links via platicon frequency microcombs - Wenting Wang; Hao Liu; Jiagui Wu; James F. McMillan; Dong IL Lee; Futai Hu; Wenzheng Liu; Jinghui Yang; Hangbo Yang; Abhinav Kumar Vinod; Yahya H. Ezzeldin; Christina Fragouli; et al. (eLight)
Abstract Coherent frequency microcombs, generated in nonlinear high-Q microresonators and driven by a single continuous-wave laser, have enabled several scientific breakthroughs in the past decade, thanks to their high intrinsic phase coherence and individual comb line powers. Here, we report terabit-per-second-scale coherent data communications over a free-space atmospheric link, using a platicon frequency microcomb, employing wavelength- and polarization-division multiplexing for next-generation optical wireless networks. Spanning more than 55 optical carriers with 115 GHz channel spacing, we report the first free-space coherent communication link using a frequency microcomb, achieving up to 8.21 Tbit/s aggregate data transmission at a 20 Gbaud symbol rate per carrier over 160 m, even under log-normal turbulent conditions. Utilizing 16-state quadrature amplitude modulation, we demonstrate retrieved constellation maps across the broad microcomb spectrum, achieving bit-error rates below both hard- and soft-decision thresholds for forward-error correction. Next, we examine a wavelength-division multiplexing free-space passive optical network as a baseline for free-space fronthaul, achieving an aggregate data rate of up to 5.21 Tbit/s and a field-tested spectral efficiency of 1.29 bit/s/Hz in the microcomb-based atmospheric link. We also quantify experimental power penalties of ≈ 3.8 dB at the error-correction threshold, relative to the theoretical additive white Gaussian noise limit. Furthermore, we introduce the first-ever demonstration of master–slave free-space carrier phase retrieval with frequency microcombs, and the compensation for turbulence-induced intensity scintillation and pointing error fluctuations, to improve end-to-end symbol error rates. This work provides a foundational platform for broadband vertical heterogeneous connectivity, terrestrial backbone links, and ground-satellite communication.